Effect of Wheat Flour and Modified Canna Flour Proportions and Glycerol Monostearate (GMS) Addition on the Physicochemical and Sensory Characteristics of Sweet Bread - Ramadhanty, Indira Putri; Rosida (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Canna flour is a processed product derived from Canna edulis Kerr and can potentially be an alternative local carbohydrate source. It contains high starch content, ranging from 80–90%, with amylose levels around 20–30%. Modification of canna flour is carried out to address its limitations when used in sweet bread applications. Glycerol monostearate (GMS) aids in improving the volume expansion of sweet bread made with substitute flour. This research aimed to determine the effect of the proportion of wheat flour and modified canna flour on the physicochemical and sensory characteristics of sweet bread. This research used a completely random setup with two factors: the mix of wheat flour and modified canna flour in ratios of 90:10, 80:20, and 70:30, and the amount of GMS added at 3%, 4%, and 5%. The results of the research indicate that the optimal treatment involves a proportion of 90% wheat flour and 10% modified canna flour, along with the addition of 5% GMS, namely moisture content 26.24%, ash content 2.40%, fat content 3.48%, protein content 4.88%, carbohydrate content 63%, and sensory value with color 3.60, aroma 2.44, taste 2.60, and texture 2.90. Contribution to Sustainable Development Goals (SDGs):SDG 2 – Zero HungerSDG 12 – Responsible Consumption and ProductionSDG 9 – Industry, Innovation and InfrastructureSDG 3 – Good Health and Well-beingSDG 8 – Decent Work and Economic Growth